Sistem Sistem Monitoring Telemedis untuk Pengukuran Tekanan Darah Berbasis Internet of Things (IoT) menggunakan MPX5700DP dan Jaringan LoRaWAN - Gusnam, Mu'thiana; Oktani, Dessy; Mahdaliza, Rahmi; Kamarudin, Kamarudin; Wicaksono, Muhammad Jaka Wimbang; Pasaribu, Cindy Kristine; Hutagaol, Rudcayanti; Ferdinan, Wisnu (Journal of Applied Electrical Engineering, 2024)
The telemedicine monitoring system enables independent blood pressure monitoring that can be conducted by patients in real-time and remotely monitored by medical professionals through an Android application and Firebase web platform. This research aims to monitor blood pressure measurements using the MPX5700DP sensor connected to a LoRaWAN network. The results show that this device is capable of transmitting blood pressure values with high accuracy, with the systolic value having an accuracy of 97.5% and an error percentage of 2.5%, and the diastolic blood pressure showing an accuracy of 96.8% and an error percentage of 3.2%. The IoT-based telemedicine system for blood pressure monitoring with LoRa technology has the potential to enhance early detection and management of hypertension, as well as provide better access for both patients and healthcare professionals.